2018
DOI: 10.1089/pho.2017.4369
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Smear Layer Removal Efficacy of Er:YAG Laser Irradiation by Photon-Induced Photoacoustic Streaming in Primary Molar Root Canals: A Preliminary Study

Abstract: These findings suggest that Er:YAG laser by PIPS-activated irrigation can be considered as an effective irrigant agitation technique in pediatric endodontics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
17
0
3
Order By: Relevance
“…The laser energy exploited with the LAI (laser-activated irrigation) methods has been claimed to improve the effectiveness of endodontic irrigants [11,24,25]. The recent PIPS laser technique has the peculiarity of being based on sub-ablative photoacoustic rather than photothermal phenomena, lowering the risk of scaling the dentinal surface [26,27]. The low energy levels (between 20 and 50 mJ), with a frequency between 10 and 15 Hz and with very short pulses (50 ms), generate photoacoustic shockwaves [17].…”
Section: Discussionmentioning
confidence: 99%
“…The laser energy exploited with the LAI (laser-activated irrigation) methods has been claimed to improve the effectiveness of endodontic irrigants [11,24,25]. The recent PIPS laser technique has the peculiarity of being based on sub-ablative photoacoustic rather than photothermal phenomena, lowering the risk of scaling the dentinal surface [26,27]. The low energy levels (between 20 and 50 mJ), with a frequency between 10 and 15 Hz and with very short pulses (50 ms), generate photoacoustic shockwaves [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since bacterial cells in biofilms are more resistant to disinfectants and physical effects compared with their planktonic counterparts, clinicians face a challenge in elimination of those from the root canals (Korkut, Torlak, Gezgin, Ozer, & Sener, ; Torlak & Sert, ). Considering that confocal microscopy cannot visualize the biofilm at the root canal due to high thickness of the sample of >5 mm, we used green fluorescence under fluorescence microscope as the staining method for detection (Mohmmed et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Uses of 17 % EDTA activated by PIPS during the irrigation protocol and after mechanical instrumentation resulted in better cleaning and smear layer removal when compared to other irrigation techniques [105,106]. Further studies have supported these findings and confirmed that the best results were obtained when PIPS used in combination with 17% EDTA [107][108][109][110].…”
Section: Using Laser To Remove Smear Layermentioning
confidence: 95%